Análisis multi-temporal del cambio de uso del suelo en el cantón Zapotillo, provincia de Loja - Veliz Requena, Fredy Salvador (2015)
In this study, a multi-temporal analysis of land change use took place over a period of ten years in Zapotillo, province of Loja. In order to carry it out, a methodology that combines the use of classification techniques using satellite images, Geographic Information System (GIS) and statistical analysis was used so as to examine the changes in the area and identify thesoil cover which is being exposed to greater pressure from human activities. The method uses the analysis of a cross-tabulation matrix, which provides information about the surface of the different soil covers that have remained unchanged that is to say the persistence, profit and loss and exchanges between thematic classes. The classification results determined the net changes which allow to calculate the annual deforestation total average and the annual change rate. Total changes were also calculated in order to know the real transitions between land uses. Once this methodology was applied, it was found that in the study area significant regeneration and degradation changes in the use of soil have been produced. The dense forest surface increases by 1.85% (2 241.43 ha), from 22 758.59 ha in 2000 to 25 000, 02 ha in 2010, but; the remaining assets of vegetation have decreased which means that some of these soil covers have become dense forest, and the counterparty has become agricultural areas where crops in this period of analysis have had a growth rate of 6 025.73 ha (4.97%.) Atthebeginning of the analysis this area had 9 698.13 ha(t1). Grasslands have duplicated iefrom 0.08% to (t2) to 0.16% in compare to the extension of the Zapotillocanton. Also, infrastructure presents a significant growth of 0.10% (125.42.) Also, unprotected soils have reached an extension of 137.47in these last ten years. A modelling for the year 2025 was performed using these results which were generatedby supervised classification, which allows to know the future scenario based on the changes observed in this investigation, where it is predicted that the dense forest in the Zapotillo canton will increase by 1.90% (2 324.34 ha) in compare to 2010. The rest of the remaining vegetation continues the trend observed in the results of the multi-temporal analysis that is likely to shrink. But cropswill present a significant growth of 6 093.15 ha which in relation to the extension of the cantonwill represent 17.99%. Finally, the total average annual deforestation in the Zapotillo canton is 191.80 ha and the annual exchange rate is 2,45%.